1997
DOI: 10.1002/(sici)1099-0739(199710/11)11:10/11<903::aid-aoc658>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of butyltin compounds in mussels in Canada

Abstract: The presence of the highly toxic antifouling agent tributyltin (TBT) and its degradation products was determined in four species of mussels collected from 34 locations in fresh water in Ontario and in sea water on Canada's west and east coasts. The purpose of the study was to establish baseline information in order to assess TBT trends in mussels after the 1989 Canadian regulation of antifouling uses of TBT. In fresh water, concentrations of TBT were much higher in zebra mussels (Dreissena polymorpha) than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 40 publications
2
19
0
1
Order By: Relevance
“…The widespread occurrence of imposex in Japanese gastropods has been found recently as a consequence of organotin pollution (Horiguchi, Shiraishi, Shimizu, Yamazaki, & Morita, 1995;Horiguchi, Hyeon-Seo, Shiraishi, Shibata, Soma, Morita et al, 1998). In addition to being a problem in Japan, marine organisms and seawater highly contaminated with butyltins have been reported during the last few years from the coastal waters of developed countries such as Spain, Ireland, the UK, France, Germany, USA and Canada (Chau, Maguire, Brown, Yang, Batchelor, & Thompson, 1997;Minchin & Minchin, 1997;Morcillo & Porte, 1998;Michel & Averty, 1999;Elgethun, Neumann, & Blake, 2000;Nehring, 2000;Thomas, Fileman, Readman, & Waldock, 2001;Power & Keegan, 2001;Michel, Averty, Andral, Chiffoleau, & Galgani, 2001), which have legislation similar to that in Japan. Furthermore, even higher trophic level organisms such as marine mammals and fish-eating birds from coastal areas of Japan and other developed nations, including USA and European countries, accumulated butyltin compounds at mg/g concentrations (Iwata, Tanabe, Miyazaki, & Tatsukawa, 1994;Kim, Tanabe, Iwakiri, Tatsukawa, Amano, Miyazaki et al, 1996;Guruge, Tanabe, Iwata, Tatsukawa, & Yamagishi, 1996;Kannan, Senthilkumar, Loganathan, Takahashi, Odell, & Tanabe, 1997;Tanabe, Prudente, Mizuno, Hasegawa, Iwata, & Miyazaki, 1998;Law, Blake, & Spurrier, 1999).…”
Section: Introductionsupporting
confidence: 60%
“…The widespread occurrence of imposex in Japanese gastropods has been found recently as a consequence of organotin pollution (Horiguchi, Shiraishi, Shimizu, Yamazaki, & Morita, 1995;Horiguchi, Hyeon-Seo, Shiraishi, Shibata, Soma, Morita et al, 1998). In addition to being a problem in Japan, marine organisms and seawater highly contaminated with butyltins have been reported during the last few years from the coastal waters of developed countries such as Spain, Ireland, the UK, France, Germany, USA and Canada (Chau, Maguire, Brown, Yang, Batchelor, & Thompson, 1997;Minchin & Minchin, 1997;Morcillo & Porte, 1998;Michel & Averty, 1999;Elgethun, Neumann, & Blake, 2000;Nehring, 2000;Thomas, Fileman, Readman, & Waldock, 2001;Power & Keegan, 2001;Michel, Averty, Andral, Chiffoleau, & Galgani, 2001), which have legislation similar to that in Japan. Furthermore, even higher trophic level organisms such as marine mammals and fish-eating birds from coastal areas of Japan and other developed nations, including USA and European countries, accumulated butyltin compounds at mg/g concentrations (Iwata, Tanabe, Miyazaki, & Tatsukawa, 1994;Kim, Tanabe, Iwakiri, Tatsukawa, Amano, Miyazaki et al, 1996;Guruge, Tanabe, Iwata, Tatsukawa, & Yamagishi, 1996;Kannan, Senthilkumar, Loganathan, Takahashi, Odell, & Tanabe, 1997;Tanabe, Prudente, Mizuno, Hasegawa, Iwata, & Miyazaki, 1998;Law, Blake, & Spurrier, 1999).…”
Section: Introductionsupporting
confidence: 60%
“…Consequently, many of these compounds are detectable in the environment (Kolpin et al 1998(Kolpin et al , 2002Benotti et al 2009). For example, tributyltin, an anti-estrogenic biocide, has been identified in sediment and mussel tissue collected from sites across North America (Chau et al 1997;Landmeyer et al 2004), and 17a-and 17b-trenbolone, androgenic metabolites of the veterinary pharmaceutical trenbolone acetate, have been identified in samples from discharge and downstream sites of cattle feeding operations (Durhan et al 2006). The presence of REDCs in the environment poses a potential threat to the health of humans and wildlife, as exposures can alter sexual development, reduce reproductive output, and induce behavioral changes (Ankley et al 2002;Jensen et al 2006;Salierno and Kane 2009;Dammann et al 2011;Fowler et al 2012;Gore et al 2015;Musteieles et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Another survey on the BTs contamination in seafood from selected cites along Bohai Sea by Zhou et al (2001) revealed that the TBT ranged from b6.9 to 17,175 ng Sn/g on wet weight basis and Dalian was the most seriously polluted area by TBT. When compared the present results with other coastal sites worldwide, it was found that BTs levels in Bohai coast are similar to those in developing Asian countries such as Korea (Hong et al, 2002), Philippines (Prudente, 1999) and Thailand (Kan-atireklap et al, 1998), but higher than those in some TBT antifouling paints-banned countries such as USA (Uhler et al, 1993), Austria (Hong et al, 2002), Canada (Chau et al, 1997) and Japan (Harino et al, 1998). So the BTs contamination in Bohai Sea is rather severe and urgent control or management should be reacted as soon as possible.…”
Section: Discussionmentioning
confidence: 99%